2017
DOI: 10.1111/all.13331
|View full text |Cite
|
Sign up to set email alerts
|

Different functional genes of upper airway microbiome associated with natural course of childhood asthma

Abstract: These data suggest that alterations in the composition and function of the upper airway microbiome could be related with the natural course of asthma in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 49 publications
4
33
0
Order By: Relevance
“…But the opposite is not true. This supports the previous studies that Parvimonas abundance changed in subjects with pulmonary disease (e.g., asthma or COPD) comparing to the control group (Pragman et al, 2012;Kim et al, 2017). However, either Prevotella or Porphyromonas lost its significance when adjusting for the other.…”
Section: Simulation Resultssupporting
confidence: 90%
“…But the opposite is not true. This supports the previous studies that Parvimonas abundance changed in subjects with pulmonary disease (e.g., asthma or COPD) comparing to the control group (Pragman et al, 2012;Kim et al, 2017). However, either Prevotella or Porphyromonas lost its significance when adjusting for the other.…”
Section: Simulation Resultssupporting
confidence: 90%
“…But the opposite is not true. This supports the findings of the previous studies that Parvimonas abundance changed in subjects with pulmonary disease (e.g., asthma or COPD) compared to the control group (Kim et al, 2018;Pragman, Kim, Reilly, Wendt, & Isaacson, 2012). However, either Prevotella or Porphyromonas lost its significance when adjusting for the other.…”
Section: Analysis Of Longitudinal Pulmonary Microbiome Datasupporting
confidence: 91%
“…The missing covariate is imputed by its mean. This supports the findings of the previous studies that Parvimonas abundance changed in subjects with pulmonary disease (e.g., asthma or COPD) compared to the control group (Kim et al, 2018;Pragman, Kim, Reilly, Wendt, & Isaacson, 2012). However at the phylum level, Bacteroidetes shows a significant association with spirometry while Firmicutes shows a significant association with diffusing capacity measures.…”
Section: Analysis Of Longitudinal Pulmonary Microbiome Datasupporting
confidence: 90%
“…A systematic review and meta‐analysis indicates that the intake of vitamin D during pregnancy, as measured from 25‐hydroxyvitamin D levels, is associated with a reduction in the offspring's respiratory tract infections but there is no supporting evidence on a beneficial effect on asthma or allergies . The airway microbiota composition in children is different in healthy, asthmatic, and remission groups . The severity of bronchial hyperresponsiveness is associated with the presence of specific bacteria, upregulation of inflammatory genes, and lack of anti‐inflammatory prostaglandin E2 genes in the airway microbiome of asthmatic children.…”
Section: Prediction and Prevention Of Allergic Diseasementioning
confidence: 99%
“…54 The airway microbiota composition in children is different in healthy, asthmatic, and remission groups. 55 The severity of bronchial hyperresponsiveness is associated with the presence of specific bacteria, upregulation of inflammatory genes, and lack of anti-inflammatory prostaglandin E2 genes in the airway microbiome of asthmatic children. A three-generational cohort study has recently shown that children whose maternal grandmother smoked during pregnancy are at higher risk of developing early persistent childhood asthma.…”
Section: Pred Ic Ti On and Pre Venti On Of Allerg I C D Is E A S Ementioning
confidence: 99%